Iron nutritional efficiency, cycling and export in oil palm cultivated at different ages - Viégas, Ismael de Jesus Matos; Marques de Lima, Maria Joseane; da Silva Amaral, Lídia; Garcia Costa, Milton [UNESP]; Costa Santos, Líbina; Ferreira, Eric Victor de Oliveira (Taylor & Francis, 2024)
Iron (Fe) plays a fundamental role in the nutrition of plants, yet its role in oil palm remains understudied. This study aims to unlock the role of Fe by analyzing its cycling and export different stages of oil palm tree growth. The experiment was conducted in Thailand, Pará State (Brazil), in a dystrophic Yellow Ferralsol, in a split-block, with four replications and seven treatments (plant age; 2, 3, 4, 5, 6, 7, and 8). The concentration, accumulation, recycling, immobilization, and export of Fe were evaluated, in addition to Fe use efficiency, in all plant organs. Analysis of variance (p < 0.05) was carried out on the results and regression model adjustments. The concentration and accumulation of Fe in the stem was greatest at the eighth year of the plants, and the fruit had higher Fe export values in the eighth year of the oil palm as well. As plants aged, the Fe concentration, accumulation, export, and use efficiency increased. Oil palm accumulates and immobilizes more Fe in its organs than it exports, a fact that contributes to the cycling and nutrition of the Fe in the plant. This research paves the way for future studies to explore how Fe can be optimized in oil palm trees to unlock their full potential.
Keywords: Amazon; Elaeis guineensisJacq; nutritional diagnosis; oil seed; palm tree